CLIMAHARMONY: INTEGRASI PINTAR KONTROL SUHU DAN KELEMBABAN DALAM GREEN HOUSE UNTUK PERTANIAN BERKELANJUTAN BERBASIS WEMOS ESP8266 - Sahabman Tua Pardamean Naibaho; Eva Diah Zanuarini; Wanda Antika Sari; Ulil Ulya Fadlilah (TURBO [Tulisan Riset Berbasis Online], 2026)
This research aims to develop an effective automatic control system for managing temperature and humidity within a greenhouse to support sustainable agriculture. The system utilizes the Wemos ESP8266 microcontroller as the central control unit, responsible for monitoring and regulating environmental conditions in real-time. The DHT22 sensor is used to measure temperature and humidity, while the actuators consist of fans, exhaust fans, and misting nozzles. The ergonomically designed greenhouse, measuring 3m x 2m, is equipped with four fans and four nozzles to control temperature and humidity. It also features UV-coated walls that allow light to penetrate while protecting plants from pests. The Climaharmony humidity control system performed well, maintaining an average humidity of 77.77% RH with minimal fluctuation (standard deviation of 0.49% RH), staying within the ideal range of 65%-78% RH. Similarly, the temperature control system recorded an average temperature of 28.46°C, with small fluctuations (standard deviation of 0.92°C), also within the optimal range of 20°C to 30°C. Overall, the conditions inside the greenhouse were conducive to the growth of lettuce plants. Based on the research conducted on August 30 and 31, 2024, the humidity within the greenhouse has not yet reached optimal stability. It is recommended that future research use higher-dimention fans to improve humidity control. Keywords: Greenhouse, automated control, temperature, humidity, Wemos ESP8266